Supervised preoperative walking on increasing early postoperative stamina and mobility in older adults with frailty traits: A pilot and feasibility study. Issue 4 (20th July 2022) - Rampam, Sanjeev; Sadiq, Hammad; Patel, Jay; Meyer, David; Uy, Karl; Yates, Jennifer; Schanzer, Andres; Movahedi, Babak; Lindberg, James; Crawford, Sybil; Gurwitz, Jerry; Mazor, Kathleen; et al.
Abstract: Background and Aims: Frail older adults are more than twice as likely to experience postoperative complications. Preoperative exercise may better prepare these patients through improved stamina and mobility experienced in the days following surgery. We measured the impact of a walking intervention using an activity tracker and coaching on postoperative stamina, and mobility in older adults with frailty traits. Methods: We included patients aged 60+ and scoring 4+ on the Edmonton Frailty Scale. We then randomized patients to intervention versus control stratified by anticipated hospital stay (1 night vs. 2+ night) and baseline stamina (i.e., 6‐min walk distance [6MWD]). Intervention patients received an activity tracker and linked smart phone. An athletic trainer (AT) prescribed a daily step count goal and titrated this up after checking in with patients during weekly telephone calls. Controls received general walking recommendations. We then measured postoperative 6MWD 1–3 days after surgery. We also assessed postoperative mobility by measuring steps walked the day after surgery using a thigh‐worn monitor. Because many patients could not walk postoperatively, we compared intervention‐control difference in both 6MWD and steps using Wilcoxon rank testing and Tobit and ordinal logistic regression adjusting for several patient characteristics. Results: We randomized 104 eligible patients; 80 patients remained for final analysis. There was no difference in intervention versus control postoperative 6MWD (median 72 vs. 74 m Wilcoxon p  = 0.54) or postoperative steps taken (median 128 vs. 51 steps Wilcoxon p  = 0.76). Analysis adjusting for patient characteristics was consistent with these findings. Conclusion: Our intervention consisting of goal setting with an activity tracker and telephonic coaching by an AT did not appear to improve stamina or mobility measured in the days after surgery. Small sample size limited our ability to examine this impact in subsets defined by surgical specialty or baseline stamina.